Barriers and Enablers to Accessing Mental Health Services for People With Intellectual Disability: A Scoping Review. Issue 1 (2nd January 2018) - Whittle, Erin Louise; Fisher, Karen R.; Reppermund, Simone; Lenroot, Rhoshel; Trollor, Julian
ABSTRACT: Background : It is well established that people with an intellectual disability have high rates of mental health problems, yet rates of uptake of services do not match need. Aim : To identify the current literature pertaining to the barriers and facilitators to access to mental health services for people with an intellectual disability. Method : A systematic search identified English-language articles that addressed barriers or enablers to access, mental health services, and intellectual disability from 2005 to 2016. Results were synthesized according to Gulliford et al.'s four dimensions of access: availability, utilization, relevance and effectiveness, and equity. Results : Barriers and enablers were identified across all the dimensions. Organizational barriers, lack of services, and poor-quality services related to deficits in knowledge were among the barriers discussed in the literature. Facilitators included emphasis on interagency collaboration, and training and education. Substantial gaps were also identified, particularly in relation to the lived experience of these barriers. Conclusions : Further research and evaluation across all aspects of access to mental health care for people with an intellectual disability is needed.